The Guterres Disarmament Agenda and the Challenge of Constructing a Global Regime for Weapons - Randy Rydell (Journal for Peace and Nuclear Disarmament, 2020)
On 24 May 2018, United Nations Secretary-General António Guterres launched his new “disarmament agenda” in an address at the University of Geneva. The UN’s Office for Disarmament Affairs (UNODA) simultaneously released a 73-page “non-paper” that elaborated this new agenda. In October 2018, UNODA issued the agenda’s implementation plan. This article will describe the key themes and specific proposals of this disarmament initiative. It will identify those features that represent both continuity and change relative to past proposals by other Secretaries-General. It will also discuss the agenda’s initial impacts, obstacles encountered, and future opportunities for progress. Finally, it will offer some reflections on the broader role of the United Nations, its Secretariat, and its Secretary-General in advancing global disarmament objectives.